2012
DOI: 10.1128/jcm.00481-12
|View full text |Cite
|
Sign up to set email alerts
|

A New Loop-Mediated Isothermal Amplification Method for Rapid, Simple, and Sensitive Detection of Leptospira spp. in Urine

Abstract: We developed a new loop-mediated isothermal amplification (LAMP) method to detect rrs , a 16S rRNA gene of pathogenic Leptospira spp. in urine. The method enables detection of two leptospiral cells per reaction mixture following boiling of urine specimens. The sensitivity of this method is higher than that of culture or of flaB nested PCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 18 publications
3
59
0
Order By: Relevance
“…A retrospective study was performed in 135 patients admitted to San Lazaro Hospital (Manila, Philippines) in 2012 with clinical suspicion of leptospirosis; 112 of them were confirmed positive with one of following diagnostic tools using serum or urine samples: the microscopic agglutination test [37], immunochromatographic assay (Standard Diagnostics, Yongin, Korea), enzyme-linked immunosorbent assay (ELISA; Diagnostic Automation, Calabasas, CA, USA), loop-mediated isothermal amplification, and real-time PCR [13,38]. The remaining 23 patients were confirmed to have non-leptospirosis illnesses of unknown origin and served as controls.…”
Section: Methodsmentioning
confidence: 99%
“…A retrospective study was performed in 135 patients admitted to San Lazaro Hospital (Manila, Philippines) in 2012 with clinical suspicion of leptospirosis; 112 of them were confirmed positive with one of following diagnostic tools using serum or urine samples: the microscopic agglutination test [37], immunochromatographic assay (Standard Diagnostics, Yongin, Korea), enzyme-linked immunosorbent assay (ELISA; Diagnostic Automation, Calabasas, CA, USA), loop-mediated isothermal amplification, and real-time PCR [13,38]. The remaining 23 patients were confirmed to have non-leptospirosis illnesses of unknown origin and served as controls.…”
Section: Methodsmentioning
confidence: 99%
“…The studies included were conducted in different countries and were published from 1992 to 2018. Some of the included studies used different methods; thus, the data were reported as separate independent studies [12,[22][23][24][25][26][27][28][29][30][31][32].…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…The sensitivity of this method is higher than those of culture or of flaB-nested polymerase chain reactions (Koizumi et al 2012). The combination of DNA detection and antibody detection will enhance the accuracy for diagnosis of leptospirosis (Iwasaki et al 2016).…”
Section: Loop-mediated Isothermal Amplification Assay As Point-ofcarementioning
confidence: 99%